ANALISIS PENGEMBANGAN KOMPETENSI PEGAWAI PADA DINAS PENDIDIKAN DI KOTA MAKASSAR - Muhammad Faisal (Jurnal Pallangga Praja (JPP), 2020)
This study aims to determine the development of employee competenceincluding the development of skills, knowledge, and attitude of employeesat the Department of Education Makassar. The research used qualitativedecriptive approach with the research informant is Head of Department,Secretary, Head of Division, and Head of Sub Division of General and Personnel as well as employees at Education Department of MakassarCity. Data were collected by interview, observation and documentationtechnique, then the data were analyzed by three stages: data reduction,data display and verification / drawing conclusion. The results of the studyexplain that the development of employee skills in the form of leadership,functional and technical training. The development of employee competencein terms of knowledge development can be seen from formal education, nonformal education, the appropriateness of discipline, and work experience.The development of employee competence in terms of employee attitudedevelopment can be seen from the activities of independence, spirituallecture, direction, sanction, and appreciation.